Simulation of a vibratory system with shape memory alloy under rotating unbalance excitation - Silva, Michel (2022)
This paper presents a numerical simulation of the non-linear dynamic presented by a mechanical vibratory system (MVS) under rotating unbalance and dumped by shape memory alloy (SMA). To do so, a Matlab code was used to solve the respective equations. The results made clear the dissipative capability of this material due its hysteretic behavior.